Comparison of lipids from Spiroplasma citri and corn stunt spiroplasma. - Patel, K R (1978)
The qualitative lipid composition of Spiroplasma citri and corn stunt spiroplasma is identical. Small amounts of acylated glucose and steryl glucoside were found.